Counterfactual Thinking and Entrepreneurial Self–Efficacy: The Moderating Role of Self–Esteem and Dispositional Affect. (March 2013) - Arora, Punit; Haynie, J. Michael; Laurence, Gregory A.
Scholars have suggested that counterfactual thinking may play an important role in entrepreneurship; however, empirical research positioned to inform the nature of this relationship has been equivocal. In this study, we draw on the tenets of social cognition theory as a basis to investigate the relationship between counterfactual thinking and the dispositional attributes of the entrepreneur, hypothesizing concomitant influences upon the entrepreneur's self–efficacy. Based on a survey of 138 entrepreneurs, our findings suggest that the implications of counterfactual thinking for entrepreneurial self–efficacy are moderated by individual differences based in the dispositional attributes of the entrepreneur.